INKONSISTENSI PUTUSAN MAHKAMAH KONSTITUSI TERKAIT KEWENANGAN MENGADILI SENGKETA PEMILIHAN KEPALA DAERAH (Studi Kasus Putusan Mahkamah Konstitusi Nomor 97/PUU-XI/2013 dan Putusan Mahkamah Konstitusi Nomor 85/PUU-XX/2022) - Nadhirah Putri; Emilda Firdaus; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research aims to analyze the legal considerations of the Constitutional Court judgesin deciding a decision and see the inconsistency of the Constitutional Court in interpretingConstitutional Court Decision Number 97/PUU-XI/2013 and Constitutional Court DecisionNumber 85/PUU-XX/2022.This type of research can be classified into normative juridical research. By usingsecondary data which includes primary legal materials, secondary legal materials, and tertiarylegal materials and data collection techniques using literature studies. This research also usesqualitative data analysis and draws conclusions deductively.From the results of research on the problem, First, in the Constitutional Court DecisionNumber 97/PUU-XI/2013, the Constitutional Court judges considered that regional elections arenot included in the electoral regime as regulated in the 1945 Constitution of the Republic ofIndonesia, then in the Constitutional Court Decision Number 85/PUU-XX/2022, theConstitutional Court judges consider that there is no distinction between election and regionalelection regimes. Second, the cause of the Constitutional Court's inconsistency in interpretingdecisions regarding the authority to adjudicate regional election disputes is the lack of clarity inthe 1945 Constitution regarding the regulation of elections and regional elections, differences inthe logic of thinking of Constitutional Court judges in deciding and adjudicating regionalelection disputes, changes related to the composition of the members and chairman of the panelof Constitutional Court judges in Constitutional Court Decision Number 97/PUU-XI/2013 andConstitutional Court Decision Number 85/PUU-XX/2022, and changes to statutory regulationsrelated to resolving disputes over regional head results.Keywords : Regional Head Election – Regional Head Election Dispute Resolution